Raising a thousand Tutu voices: Reflections on the Truth to Power exhibition (Acta Theologica)
This article explores the lifework and legacy of Archbishop Desmond Mpilo Tutu who passed away on 26 December 2021. It relates the reaction of visitors to the newly installed exhibition, Truth to power: Desmond Tutu and the churches in the struggle against apartheid, in the historic Old Granary Building, home of the Desmond & Leah Tutu Legacy Foundation in Cape Town. The Victims Wall forms part of the exhibition, in a room dedicated to the unfinished business of the Truth and Reconciliation Commission (TRC). The article argues that the cries and bruised bodies of the victims of apartheid, such as those of Mrs Calata, widow of Fort Calata, one of the Cradock Four victims, and of thousands of “ordinary people”, are still reverberating down the decades to be heard and acknowledged by specifically White South Africans. The example and the courage of the poet and journalist, Antjie Krog, who covered the TRC hearings and who is still speaking poetry to power as a public intellectual, are used to reflect on the author’s own culpability and that of other White Afrikaans-speaking South Africans and their involvement in the TRC process. The article concludes with the immense and joyful task of the Foundation to raise a thousand Tutu voices, in an attempt to answer questions on how to keep the memories of the bodies of those who suffered under colonialism and apartheid alive, while seeking reconciliation and fighting for a just, equal, and inclusive society in a deeply divided South Africa and how to become more fully human